Talent pool for Global Business Services: industry-academia collaboration - Aini Aman,; Yusasniza Mohd Yunus,; Ruhanita Maelah,; Zaini Embong,; Zakiah Muhammaddun Mohamed,; Syaima’adznan,; Ab Aziz Ahmad,; Zarith Nurzarifah,; Dahlia Fernandez, (Penerbit Universiti Kebangsaan Malaysia, 2017)
In the rapid development of Global Business Services (GBS) industry, there is a need to nurture quality and capable talent pool. One of the efforts is through industry-academia collaboration in offering of GBS course at the university. Universiti Kebangsaan Malaysia (UKM) together with TalentCorp and Malaysia Digital Economy Corporation (MDEC) collaborativelydeveloped the first GBS course in Asia. The course consists of three days of intensive seminar and ten weeks of case study project. Both seminar and case study project require direct interaction with GBS firms. The purpose of this paper is to assess the challenges of offering the GBS course faced by its stakeholders. Based on data gathered through survey and roundtable discussions, this paper presents challenges in delivering the course content and achieving the course objectives. Findings suggest that the main challenges are commitment, time management and students’ preparation. Despite these challenges, the course has direct impacts on the stakeholders as the GBS course heightens awareness on GBS industry among future graduates and helps increase their employability in the industry.